Comparing the Efficiency of Turkish and Azerbaijani Banks: An Application with Data Envelopment Analysis - Yüksel, Serhat; Mukhtarov, Shahriyar; Mammadov, Elvin (International Journal of Economics and Financial Issues, 2016)
In this paper, we made a comparison about the efficiency of Turkish and Azerbaijani banks. Within this scope, we analyzed 10 biggest banks of both countries regarding asset size. Furthermore, data envelopment analysis (DAE) was used for the data between 2010 and 2014 in this study. As a result of analyzing 5 inputs and 3 outputs, it was determined that Turkish banks are more efficient than Azerbaijani banks. Out of 10 Turkish banks, only Türkiye Ekonomi Bankası was not efficient in 2011 whereas other banks were efficient for all years. On the other hand, it was defined that only 4 Azerbaijani banks were efficient for all years whereas other 6 banks were not efficient for some years during this period. Keywords: data envelopment analysis, Turkey, Azerbaijan, banks, efficiency JEL Classifications: G21, H21